Exploring the role of identity in pro-environmental behavior: cultural and educational influences on younger generations - Wild, Steffen; Schulze Heuling, Lydia (Frontiers in Psychology, 2024)
It is of paramount importance to gain an understanding of pro-environmental behavior if we are to successfully tackle the climate crisis. The existing body of research provides evidence that identity influences pro-environmental behavior. However, such research is often over-generalised and researchers are challenged to conduct robust analyses with regard to specific local, cultural and educational factors. The present study aims to investigate whether personal or social identity has a distinct effect on three different dimensions of pro-environmental behavior, using the principles of self-categorisation theory. Additionally, the study seeks to determine whether one of these two factors, the individual or the social factor, is predominant over the other. The study group consisted of cooperative students in Germany, typically a group with high professional ambitions. The data was collected in a cross-sectional survey with a total of 568 cooperative students from academic disciplines in engineering and economics. The reliability of the scales is satisfactory (ω = 0.76–0.88), and the hypotheses are tested by estimating structural equation models. Our research demonstrates that while social identity exerts a stronger influence on activist behavior than personal identity, personal identity has a more pronounced effect on consumer behavior than social identity. Nevertheless, no general statement can be made regarding the relative strength of the effects of personal and social identity on pro-environmental behavior dimensions.